On some expansions for the multidimensional stable densities with parameter α>1 - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. Калинаускайте. Некоторые разложения плотностей многомерных устойчивых распределений с показателем α>1 N. Kalinauskaitė. Kai kurie daugiamačių stabilių tankių su rodikliu α>1 skleidiniai